Treatment-related pure large-cell neuroendocrine carcinoma of the prostate with systemic metastases in a young adult: a rare case report - Zhang, Baolin; Zhu, Yifan; Huang, Renpeng; Zhou, Feng; Ling, Zhixin (Frontiers in Oncology, 2025)
Large cell neuroendocrine carcinoma of the prostate is an extremely rare malignant subgroup with limited reported cases. Little is known about its pathological characteristics, treatment options and long-term prognosis. In this case, we report a young patient presenting with painless gross hematuria for 3 months, accompanied with elevated serum total prostate-specific antigen (tPSA) level of 83.7 ng/ml. Magnetic resonance imaging (MRI) and 18F-FDG Positron Emission Tomography - Computed Tomography (¹8F-FDG PET/CT) indicated giant prostate mass, which metastasized to bilateral lungs, bones and lymph nodes. Prostate biopsy and transurethral resection of the prostate confirmed the diagnosis of adenocarcinoma with a Gleason score of 4 + 5. After receiving 12 months of goserelin acetate, rezvilutamide and six cycles of docetaxel, the patient further underwent laparoscopic radical prostatectomy (LRP). Immunohistochemical analysis (Syn+/CgA+/AR−) combined with treatment history revealed a histopathological diagnosis of treatment-related LCNEPC. Subsequently, the patient then received immunotherapy with serplulimab (300 mg) and the EP regimen (combining etoposide and cisplatin) chemotherapy. After six cycles of chemo-immunotherapy, further examination indicated reduction in size of multiple lymph nodes and lung metastases by March 2025. Here we reported a rare case of treatment-related LCNEPC, who had experienced systematic therapy with comprehensive care. These diagnostic and therapeutic approaches may improve the management capability and highlight the critical role of multimodal strategies in the subsequent cases.